Anti-Fungal Activity Test Of Cardamom (Amomum Cardamomum L.) Leaf Ethyl Acetate Fraction Against Candida Albicans And Pityrosporum Ovale - Nuranti Rumela; Manahan Situmorang; Martin Suhendri; Aditiya Mawarni Zega (Journal of Innovative and Creativity, 2025)
Cardamom leaves (Amomum cardamomum (L.) Cardamom is a plant that is commonly used as a cooking spice and is also believed to have properties for treating various diseases, one of which is disease caused by fungi. The aim of this research is to determine the antifungal activity of ethanol extract of cardamom leaves against fungi Candida albicans and Pythyrovorum ovale to determine the effective inhibitory concentration of the ethanol extract of kitolod leaves in inhibiting it as an antifungal. The samples were extracted by the maceration method using 96% ethanol solvent. The antifungal activity test was carried out by the agar diffusion method using a paper backer. This experiment  consisted of three times Mixtures with respective concentrations of 20%, 40%, 80%, DMSO 10% as a negative control and Ketoconazole as a positive control. The results of the antifungal activity test showed that the ethanol extract of cardamom leaves was against Candida albicans fungi with concentrations of 20%, 40%, 80%. % respectively had an inhibition zone of (16.67 mm), (16.77 mm), (18.09 mm), positive control ketoconazole (21.40 mm), negative control 10% DMSO (0 mm). Meanwhile, the fungus Pythyrovorum ovale with concentrations of 20%, 40%, 80% respectively had an inhibition zone of (13.78 mm), (14.35 mm), (16.18 mm), positive control ketoconazole (19.86 mm), 10% DMSO negative control (0 mm). The results of the study showed that the ethanol extract of cardamom leaves had antifungal activity against Candida albicans and Pythyrovorum ovale.